YOUTH, EDUCATION AND EMPLOYABILITY: FROM FACTORY WORK TO MONETIZED LIVES (REMUNOM, 2025)
Youth is a period of preparation for entry into working life. According to the Durkheimian view of social division, work holds a strong social meaning. Guaranteed in the 1988 Constitution of the Republic, fundamental rights represent a sphere of State action, in addition to a field of care by the family and school, for the purpose of individual formation. The aim of this essay is to analyze the relationship between youth and work by referencing historical and sociological understandings. This is an integrative literature review, utilizing primary sources from canonical Sociology authors and secondary sources from articles indexed in the CAPES portal, spanning the period from 2015 to 2025. The descriptors used were: “employability in contemporary times,” “youth and uberization,” and “work and digital influencer.” The inclusion criteria were available articles that articulate with the theme of work. Bardin’s content analysis was used for the material analysis. The solidity and longevity of factory work have been molded by new societal behaviors, particularly among the youth. Labor, once protected by legislative power, has been gradually discredited. The pursuit of uberization models is a reality among the younger generation. It is imperative to understand these new occupational choices—currently romanticized in mass media as a social phenomenon—in order to ensure that this generation has prospects for a consolidated future protected by the State. Analyzing the historical context, labor relations have undergone radical changes. The current dynamic reflects the fluidity of contemporary capitalism, moving from the rigidity of the factory to the precarity of monetized lives. New occupations, consolidated in various labor practices, are emerging in a process of globalized and hyper-connected adaptation, redefining not only employment but also identities and aspirations.